2019
DOI: 10.5688/ajpe7106
|View full text |Cite
|
Sign up to set email alerts
|

Training Student Pharmacists in Medication Dispensing and Checking Within a High-Fidelity Clinical Environment

Abstract: Objective. To describe the implementation of and student pharmacist experience with high-fidelity training in medication dispensing and clinical checking processes and procedures. Methods. An actual dispensary in a large teaching hospital was used as the setting in which to provide undergraduate student pharmacists the opportunity to develop skills and knowledge regarding the process and procedures of medication dispensing and clinical checking. The sessions were facilitated by a member of the hospital pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This is similar to the use of MyDispense in Australia and United Kingdom where the program has been implemented in medication dispensing for first and second year student pharmacists. 3,14,28 On the other hand, MyDispense were used in Malaysia and Saudi Arabia by more advanced student pharmacists (eg. fourth and fifth year) in their experiential practices/clerkships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the use of MyDispense in Australia and United Kingdom where the program has been implemented in medication dispensing for first and second year student pharmacists. 3,14,28 On the other hand, MyDispense were used in Malaysia and Saudi Arabia by more advanced student pharmacists (eg. fourth and fifth year) in their experiential practices/clerkships.…”
Section: Discussionmentioning
confidence: 99%
“…3,12,13 The program allows students the opportunity to engage with the entire process of dispensing while providing interactive explanations, self-assessment, and performance feedback. 13,14 It has been used in both didactic and experiential curricula to teach topics such as medication dispensing, pharmacy skills, pharmacy law, and pharmacotherapeutics. 8,9,15 McDowell et al found that student pharmacists who used MyDispense in their dispensing tutorials reported positive perceptions of the tool to learn dispensing skills.…”
Section: Introductionmentioning
confidence: 99%
“…There is little evidence of practical situated learning in UK undergraduate pharmacy with the majority of work around legitimate peripheral practice being based around other health professions. [29][30][31] The previous iteration of this specific placement example did use situated learning, but it provided students with an opportunity to participate in tasks within a live pharmacy dispensary rather than on a ward [3]. Based on the evolving role of the pharmacist and the subsequent shift in education and training standards [1], students are required to perform at the 'shows how' and 'does' level of competence [32].…”
Section: Discussionmentioning
confidence: 99%
“…To prepare for practice and meet the training and education standards for pharmacists, pharmacy students are required to have knowledge of, and competency in, the safe supply of medicines [1]. This knowledge can be taught didactically, but simulation and/or placements are the usual method for exposing students to the practical skills required [2,3]. Simulation has many limitations, including high resource and cost requirements and limited realism, which limits transferability to practice [4,5].…”
Section: Introductionmentioning
confidence: 99%